2013
DOI: 10.1097/mao.0b013e3182979278
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal and Taste Sensations of the Tongue After Middle Ear Surgery

Abstract: These findings suggest that the electrostimulator test was most useful to objectively assess small changes of trigeminal sensation among the 3 tests. The finding that trigeminal sensitivity of the tongue deteriorated on the operated side after CTN injury suggests that CTN function affected both taste sensation and trigeminal sensation of the tongue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(57 citation statements)
references
References 9 publications
1
56
0
Order By: Relevance
“…Sakaguchi et al [2] reported that patients with an injured CTN show significant threshold differences in an electrostimulator test between the operated and nonoperated sides of the tongue. One report showed that the CTN includes somatosensory afferents [18].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sakaguchi et al [2] reported that patients with an injured CTN show significant threshold differences in an electrostimulator test between the operated and nonoperated sides of the tongue. One report showed that the CTN includes somatosensory afferents [18].…”
Section: Discussionmentioning
confidence: 98%
“…Tasting with the tongue depends on the CTN, and the tongue somatosensory function depends on the lingual nerve, which is the third branch of the trigeminal nerve. Patients with CTN injury sometimes complain of not only a taste disorder but also tongue numbness [2].…”
Section: Introductionmentioning
confidence: 99%
“…There were 46 cases with preservation of the CTN and 13 cases with sectioning of the CTN. In addition, 106 adult patients were compared with the pediatric patients, and they were included in the previous study . Of the 106 cases, 44 had cholesteatoma; 34 had chronic otitis media; and 28 had noninflammatory middle ear disease.…”
Section: Methodsmentioning
confidence: 99%
“…There have been a few reports of the changes in lingual trigeminal sensitivity after middle ear surgery. They reported that somatosensory function deteriorated on the affected side after middle ear surgery . It is generally thought that pediatric patients complain of postoperative taste function less frequently than adult patients .…”
Section: Introductionmentioning
confidence: 99%
“…Trigeminal nerve function on the tongue has been examined in a few previous reports using, for example, Semmes‐Weinstein sensory test (SW test), 2‐point discrimination, and capsaicin. Sakaguchi et al reported that postoperative thresholds in the CTN‐sectioned group and the manipulated group were significantly higher than the preoperative thresholds on the electrostimulator test and electrogustometry (EGM). They also noted that the electrostimulator was the most useful tool to objectively assess trigeminal nerve sensation, whereas the SW test had low sensitivity to assess sensory changes.…”
Section: Introductionmentioning
confidence: 98%